Comunicação pública, cidadania e internet: a popularização da ciência nos portais eletrônicos de governo - Camargo, Aline Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Public communication can embrace the important role of being a tool mediating the integration of science, technology and society. Science popularization through pul communication should be seen as a vector for social inclusion and democratization knowledge, towards a more effective practice of management and social control, pointing to the need of taking the public opinion into account as one of the most relevant indicators for the management of public policies in the area. Among the accomplishments of public communications about science and technology policies in Brazil today, we highlight the webpages of federal units of government, including specific pages of the departments of the area. Policies and programs developed by state management bodies have increasingly been released on the internet, which raises research questions about the quality of the accomplishments in public communications. This project proposes to identify the potential contribuition of digital public communication about science and technology to the strengthening of citizenship, considered in its dimension of exercising the righ to information. Specific objectvies are: a) evaluationg the quality of public communication as a digital source of information about the performance of state and federal policies on science and technology in the face of demands for social and economic development and public investment in public higher education systems; b) investigating the context and depth of information on public policies for science and technology present in e-government portals from 27 Brazilian states in relation to five categories of analysis: history and diagnoses; goals and objectives; public benefit; social impacts; and environmental impacts; c) proposing, with respect to the result achieved about the quality of the digital public communication on science and technology, communication managemetn strategies in e-government portals, directed to improve the...

A comunicação pública pode assumir o relevante papel de ser uma ferramenta mediadora da integração entre ciência, tecnologia e sociedade. A popularização da ciência através da comunicação pública deve ser vista como vetor de inclusão social e subsídio para a democratização do conhecimento, em direção a práticas de gestão e controle social mais efetivas, apontando para a necessidade de que a opinião pública seja considerada como mais um dos indicadores relevantes para a gestão de políticas públicas na área. Entre as ações de comunicação pública sobre políticas de ciência e tecnologia na atualidade no Brasil, destacam-se os portais eletrônicos de governo das unidades federativas, que incluem páginas específicas das secretarias da área. Políticas e programas desenvolvidos pelas instâncias estaduais de gestão têm sido cada vez mais divulgados na internet, o que suscita questões de pesquisa sobre a qualidade das realizações de comunicação na área. A pesquisa buscou identificar a potencial contribuição da comunicação pública digital sobre ciência e tecnologia à afirmaçã da cidadania, considerada em sua dimensão de exercício do direito à informação. Os objetivos específicos são: a) avaliar a qualidade da comunicação pública digital como fonte de informação sobre o desempenho de políticas públicas e federais de ciência e tecnologia diante das demandas de desenvolvimento social e econômico e do investimento público nos sistemas públicos de ensino superior; b) investigar o contexto e a profundidade das informações sobre políticas públicas e ciência e tecnologia presentes nos portais eletrônicos de governo das 27 unidades federativas brasileiras e do portal do Ministério da Ciência, Tecnologia e Inovação em relação a cinco categorias de análise: antecedentes e diagnósticos; objetivos e metas; públicos beneficiados; impactos sociais; impactos ambientais; c) propor...
Keywords: Comunicação; Direito à informação; Internet; Democracia; Ciencia; Communication